1.2 μm persistent luminescence of Ho3+ in LaAlO3 and LaGaO3 perovskites. Issue 42 (16th October 2018) - Xu, Jian; Murata, Daisuke; So, Byoungjin; Asami, Kazuki; Ueda, Jumpei; Heo, Jong; Tanabe, Setsuhisa
Abstract : Combination between electron traps and host phonon energy for Ho 3+ persistent luminescence in perovskites. Abstract : Persistent luminescence (PersL) in the short-wave infrared (SWIR: ∼900–1700 nm) region has attracted much attention for potential biomedical imaging and night-vision surveillance applications. Although trivalent lanthanide (Ln 3+ ) ions are considered to be one of the most promising luminescent centers working for this region, the lack of suitable persistent phosphor hosts is still the bottleneck of this field. Herein, by using the persistent energy transfer from Cr 3+ to Ho 3+, Ho 3+ PersL at 1.2 μm has been realized in both Ho 3+ –Cr 3+ –Sm 3+ tri-doped LaAlO3 (LAO:Ho–Cr–Sm) and Ho 3+ –Cr 3+ co-doped LaGaO3 (LGO:Ho–Cr) perovskites. The Ho 3+ photoluminescence (PL) intensity ratio between the 5 I6 → 5 I8 transition at ∼1.2 μm and the 5 I7 → 5 I8 transition at ∼2.0 μm in LAO is lower than that in LGO due to the higher phonon energy of the LAO host, resulting in its preferred population of the 5 I7 excited level through multi-phonon relaxation (MPR) processes. However, the LAO:Ho–Cr–Sm phosphor still exhibits superior Cr 3+ /Ho 3+ PersL intensity than that of LGO:Ho–Cr, and it is even comparable with that of the most widely used deep-red ZnGa2 O4 :Cr 3+ persistent phosphor. This can be explained by the efficient electron traps of Sm 3+ ions in LAO:Ho–Cr–Sm while this kind of sensitization by lanthanide ions seems not to work in LGO:Ho–Cr based on prediction from the vacuum referred binding energy (VRBE) diagram. These results demonstrated by the flexible ABX3 perovskites could give a vivid example to choose suitable material hosts, electron trapping centers and energy donor–acceptor combinations toward long PersL in the SWIR region.